2013
DOI: 10.1007/s10461-013-0584-z
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Maintenance Therapy Decreases the Rate of Antiretroviral Therapy Discontinuation Among HIV-Positive Illicit Drug Users

Abstract: We sought to examine whether methadone maintenance therapy (MMT) decreased rates of antiretroviral therapy (ART) discontinuation and was associated with plasma HIV RNA responses among a cohort of illicit drug users. Cumulative ART discontinuation rates were estimated using Kaplan–Meier methods and factors independently associated with ART discontinuation were identified using Cox proportional hazards regression. Engagement in MMT was negatively and independently associated with ART discontinuation [Adjusted Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…83 In Vancouver, Canada, several longitudinal studies showed not only that OST continuation improved ART adherence over time, 84 but also the converse – that OST discontinuation significantly increased the risk of ART non-adherence 85 – and that OST patients with higher opioid agonist doses had the strongest adherence to ART. 86 In China, the understanding of the importance of the OST-ART link led to an effort to integrate ART services in methadone clinics.…”
Section: Drug Policy and Infectious Diseasesmentioning
confidence: 99%
“…83 In Vancouver, Canada, several longitudinal studies showed not only that OST continuation improved ART adherence over time, 84 but also the converse – that OST discontinuation significantly increased the risk of ART non-adherence 85 – and that OST patients with higher opioid agonist doses had the strongest adherence to ART. 86 In China, the understanding of the importance of the OST-ART link led to an effort to integrate ART services in methadone clinics.…”
Section: Drug Policy and Infectious Diseasesmentioning
confidence: 99%
“…Recent studies have found that OST among PWID is associated with higher CD4+ cell count at ART initiation[71], ART initiation and access[83,84], ART medication adherence[85,86], decreases in ART discontinuation[87], and decreases in delayed care visits[88]. …”
Section: Recent Work In Interventions To Improve Outcomes For Key Popmentioning
confidence: 99%
“…It is well known that drug use can have direct deleterious consequences on an individual’s health, as well as indirect harms, for instance unsafe practices [2]. Studies have shown that drug use plays a maladaptive role in adherence to HIV treatment [35]. Antiretroviral therapy (ART) effectiveness relies on high and sustained levels of medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments are complex with various protocols, dietary restrictions, and potential side effects. Proper treatment may be hindered by factors such as homelessness, incarceration, untreated psychiatric illnesses and drug addiction [3]. HIV positive drug users tend to have a lower uptake of treatment compared to HIV positive individuals who do not use drugs [4].…”
Section: Introductionmentioning
confidence: 99%